Penerapan Metode Dakwah: Bercermin pada Kasus Cigugur - Aripudin, Acep (Jurnal Ilmu Dakwah, 2010)
The implementation of any method of dakwah has to consider its relevance with public needs. Hence, a good implementation of a method of dakwah would be based on a preceding identification of the basic problems among the target community (madâu). The dynamics of the processes of dakwah in Cigugur show that irrelevant approaches (radical ways to protect and save Islam from any foreign influences that would otherwise contaminate true Islam) tangibly resulted in undesired effects. This has led to an alternate method of dakwah (dialogical method), currently underway in Cigugur, seen to be able to save the existence and unity of Muslim community.